Root causes of blockages in pig market systems in Central Uganda: Application of causal loop diagrams - Ouma, Emily A.; Ahumuza, Ronnie; Oba, Peter; Rao, Elizaphan James Oburu (International Livestock Research Institute, 2026)
Since 2012, CGIAR and its partners have collaborated with value chain actors and stakeholders in Uganda's pork value chain to address the constraints and opportunities in the sector. Demand for pork in Uganda is the highest in the Eastern Africa region estimated at 3.4 kg per capita per annum. Fueled by the rising demand for pork, Uganda's pig population increased significantly from 3.2 million in 2008 to 7.1 million in 2021, a growth exceeding 100% (Uganda Bureau of Statistics 2024). Whilst, in 2012, the pig sector was largely 'invisible' to decision-makers and investors, the joint work of CGIAR and partners resulted in a noticeable increase in knowledge, awareness and action within the industry. For example, pork is now recognized within the meat category prioritized in the agro-industrialization program of the 4th National Development Plan.